Vis(i)tas com Ciências: Uma abordagem multidisciplinar - Forjaz, Maria Antónia; Mina, Isabel Maria Cravo Aguiar Pinto; Neves, Isabel Correia; Almeida, Mário; Pamplona, Jorge (UMinho Editora, 2026)
Published